Outcome of decompressive operative procedure in the treatment of degenerative lumbar spinal canal stenosis: experience of managing consecutive 25 cases (BIRDEM Medical Journal, 2020)
Background: Lumbar spinal canal stenosis (LSCS) is a common medical disorder due to degenerative changesin the middle age and older individual. In this condition, narrowing of lumbar spinal canal and nerve rootcanal leads to painful, debilitating compression of spinal nerves and blood vessels. Decompressive surgery inlumbar spinal canal stenosis is one of modern methods of treatment.The objective of this study was to evaluate the outcome of decompressive operative management in degenerativelumbar spinal canal stenosis.Methods: Thiswas a prospective interventional study carried out at National Institute of Traumatology andOrthopaedic Rehabilitation (NITOR) and City Hospital, Lalmatia, Dhaka from October 2012 to December2014.Total number of patients were 25 who underwent decompressive surgical procedures. Each of patientswas evaluated by the visual analogue scale (VAS) for pain, disability by using Oswestry disability index (ODI)and ModifiedMacnab Criteria (MMC)for assessment of improvement.Results: This was a prospective interventional study carried out at National Institute Of Traumatology and OrthopaedicRehabilitation (NITOR) and City hospital, Lalmatia, Dhaka from October 2012 to December 2014. Out of 25patients, 19 patients(76%)were male and 6 patients (24%) were female, age ranged from 38-65 years with the meanage 48.50 ± 8.65 years. Sixteen (64%) patients were manual worker and 9 patients (36%) were sedentary worker.Sixteen (64%) patients had multilevel stenosis and 9 patients (36%) had single level stenosis. The mean follow upduration was 1.5 years (range: 1-3 years). Mean estimated blood loss was 150ml (range : 100-200ml), meansurgery time was 130mutes (range: 80-180min) and average hospital stay was 7 days (range: 4-10 days). Only 1patient (4%) had discitis, 1 patient (4%) had superficial wound infection and 1 patient (4%) had dural tear. AsMMC, 21 (84%) patients was poor before operation and after operation at 12 months follow up 8 patients (32%)had excellent, 12 patients (48%) had good, 4 patients (16%) had fair and 1 patient (4%) had poor functionaloutcome. Mean (SD) ODI were 75.40 (± 5.01) before operation and reduced to 8.36 (± 13.54) after operation at 3rd(12 month) follow up. Mean (SD) VAS was 7.12 (± 0.86) before operation and reduced to 1.46 (± 1.31) afteroperation at 3rd (12 month) follow up. Twenty (80%) patients had satisfactory functional outcome.Conclusion: Decompressive operation is an effective, safe and acceptable method of treatment in degenerativelumbar spinal canal stenosis (LSCS).Birdem Med J 2020; 10(2): 103-107